Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

if f (x)=x^2-x-1, then f(-5)=

Sagot :

[tex]\text{Given that,}\\\\f(x) = x^2-x -1\\\\f(-5) = (-5)^2 -(-5) -1 = 25 +5 -1 = 29[/tex]

Substitute -5 for x
f(-5) = -5^ 2 - (-5) - 1
= 25 + 5 - 1
=29
Hope this helps!